The effect of health literacy enhancement program on stroke preventive behaviors among stroke patients on recovery stage - Boonchawee, Porntira; Nunthaitaweekul, Pachanut (Thai Journal of Nursing, 2024)
This quasi-experimental research is pretest- posttest control group design.The aim of this research was to determine effect of a health literacy enhancement program on stroke preventive behaviors among stroke patients on recovery stage. A sample of 60 stroke patients on recovery stage, was purposively selected and equally divided into the control group and experimental group, 30 patients in the experimental group received a health literacy enhancement program and 30 patients in the control group received routine nursing care. Research instruments included stroke preventive behavior questionnaire and health literacy questionnaire, The content validity index of 2 questionnaires are 0.93 and 0.87 respectively, reliability coefficients are 0.71 and 0.86 respectively. Data were analyzed using descriptive statistics and t-test. The results of implementation of a health literacy enhancement program caused higher stroke preventive behavior in stroke patients on recovery stage. As the results that after experiment, stroke preventive behavior of patients in the experimental group (x̄ = 64.90, SD = 5.95) were significantly higher than before experiment (x̄ = 60.20, SD = 5.65) at a statistical significance .05 (t = - 5.95, p < .001) and higher than those in the control group ( x̄ = 58.70, SD = 5.65 ) at a statistical significance .05 (t = -3.314, p < .001)